Electrochemical and electron microscopic characterization of Super-P based cathodes for Li–O2 batteries - Marinaro, Mario; Eswara Moorthy, Santhana K.; Bernhard, Jörg; Jörissen, Ludwig; Wohlfahrt-Mehrens, Margret; Kaiser, Ute (Beilstein Journal of Nanotechnology, 2013)
Aprotic rechargeable Li–O2 batteries are currently receiving considerable interest because they can possibly offer significantly higher energy densities than conventional Li-ion batteries. The electrochemical behavior of Li–O2 batteries containing bis(trifluoromethane)sulfonimide lithium salt (LiTFSI)/tetraglyme electrolyte were investigated by galvanostatic cycling and electrochemical impedance spectroscopy measurements. Ex-situ X-ray diffraction and scanning electron microscopy were used to evaluate the formation/dissolution of Li2O2 particles at the cathode side during the operation of Li–O2 cells.
Keywords: aprotic electrolyte; impedance spectroscopy; Li–O2 batteries; scanning electron microscopy